Design and development of a casual mobile game (B) - Chow, Siew Teng (Nanyang Technological University, 2021)
The video game industry has prospered amidst the COVID-19 pandemic. An increasing number of people are turning to video games as coping mechanisms for stress, anxiety, and loss of social contact. In recent research, video games, especially casual video games, were shown to have therapeutic properties, reducing the symptoms of anxiety and depression. This report illustrates the design and development of a pandemic-themed casual mobile game, intended to help alleviate the player’s anxiety and mental distress in a pandemic situation. The casual mobile game consists of 3 chapters, each containing different storylines and unique mini-games. The scope of this project encompasses the development of a playable excerpt for chapter 1 of the game. Chapter 1 consists of 1 main interface and 4 mini games. The main interface consists of a shop system, inventory system, customization system, and access to the 4 mini-games. The 4 mini-games are based on different activities the main character can engage in at home: gardening, cooking, drawing, and cleaning. This report will contain the planning and Unity implementation of the main interface and cooking mini-game, as well as the planning for the cleaning mini-game. This casual mobile game is implemented with Unity 2D (2020.1.8f1), with its graphic assets illustrated in Procreate 5 and Adobe Photoshop 2020. The development of the game includes ideation, game design, user interface design, graphic design, gameplay programming in C#, and database implementation with SQLite